EVALUATION OF TUNA FISHING GROUND IN SOUTHERN COAST OF JAVA - SUMBAWA SEA USING SATELLITE OBSERVED DATA - MOKHLAS SATIBI; TAKAHIRO OSAWA; I WAYAN ARTHANA (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
Potential fishery in territorial water of South Java - Sumbawa Sea has not been exploited maximally. Tuna is one of fisherypotency in the territorial water of South Java - Sumbawa. Tuna is the important economic value because it represent one ofexporting commodity enthused by overseas consumer.Research was conducted in the Southern Java – Sumbawa, Indian Ocean 90 S - 160 S; 1060 E - 1210 E, using fish catch data2003 – 2006. Research location is in the inclusive Region of Fishery Management IX (DKP and PKSPL, 2003). Data weretaken from a daily fish catch of PT. Perikanan Samudra Besar (PSB) Benoa Bali 2003 - 2006.Sea level anomaly (SLA) data were estimated from Altimetry satellite (Jason 1), wind speed data was from Scatterometersatellite and sea surface temperature (SST) data was from Microwave satellite.Based on the result of this research, sea level anomaly of southern coast of Java-Sumbawa was fluctuated according tomonsoon. The highest bigeye tuna fish catched was 40 tuna in June 2003 and the lowest bigeye tuna fish was 2 tuna inNovember 2005. Maximum SLA observe during southeast monsoon was 21.77 cm in august 2005, while minimum SLAobserved during southeast monsoon was -18.15 cm in October 2003. Sea surface temperature of southern coast of Java-Sumbawa also fluctuated according to monsoon. Maximum SST observed during northwest monsoon was 30.450 C in March2006, while minimum SST observed during southeast monsoon was 25.050 C in August 2006. The highest wind speed was10.20 m/sec in June 2004 and the lowest was 2.00 m/sec in October 2004. Wind direction was reversely changed according tomonsoon. Northwest wind monsoon flew eastward and southeast wind monsoon flew westward.Fish production in PT PSB had been done over 4 years since 2003, in northwest and southwest monsoon in constant areaand correlation of linier regression among estimate of fish catching using SLA, SST and wind speed had no correlation. Withfish production during southwest monsoon PT PSB set in SLA negative in different temperature of 30 C, wind speed of 2.00m/sec and with abundant of fish catched. Meanwhile in northeast monsoon that was in positive SLA the fish catching was inlow number.